Anti-Alzheimer, antidiabetic and antioxidant potential of Satureja cuneifolia and analysis of its phenolic contents by LC-MS/MS - Taslimi, P.; Köksal, E.; Gören, A. C.; Bursal, Ercan; Aras, A.; Kılıç, Ö.; Gülçin, İ. (Elsevier B.V., 2019)
Many chronic diseases such as diabetes and Alzheimer's disease are related to the type and quality of foods, which are consumed. Particularly, various plant origin products are stated as beneficial against such kind of chronic diseases with secondary metabolites such as their phenolic structures. Satureja cuneifolia is a plant, which is consumed as an herbal tea in some regions of Turkey and that's why investigate of its biological activity is important. In our study, the anti-diabetic and anti-Alzheimer potentials of the methanol and water extracts of S. cuneifolia plant were measured via some enzymes inhibition experiments as in vitro. The antioxidant ability of the same extracts was measured via radical scavenging and reducing power methods. Also, the total phenolics and flavonoids of the plant were identified. Finally, the extracts were analyzed by the LC-MS/MS analysis and the phenolic content of S. cuneifolia was clarified. © 2019 The Author(s)
Keywords: Anti-Alzheimer; Antidiabetic; Antioxidant activity; LC-MS/MS; Satureja cuneifolia